Second-order maximum principle controlled weakly singular Volterra integral equations - Gasimov, Jasarat J.; Mahmudov, Nazim I. (Polska Akad Nauk, Polish Acad Sciences, 2024)
This work studies a class of singular Volterra integral equations that are (controlled) and can be applied to memory-related problems. For optimum controls, we prove a second-order Pontryagin type maximal principle.
Keywords: second-order maximum principle; singular Volterra integral equation; optimal control; Pontryagin's maximum principle